Negative electrode material, preparation method thereof and lithium ion battery
By subjecting natural graphite particles to pore control and high-temperature heat treatment, special carbon materials are prepared, which solves the problems of capacity fading and short cycle life of natural graphite anode materials during cycling, and achieves high cycle life and fast charging performance of the material.
Patent Information
- Application Number
- CN202411850189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-16
AI Technical Summary
During the circulation process, the existing natural graphite negative electrode materials cause the generation of SEI film and the consumption of active lithium due to electrolyte penetration, resulting in continuous attenuation of capacity and short cycle life.
Through the pore control treatment of natural graphite particles, reduce the volume of the pores and adjust the pore diameter distribution, combine high temperature thermal treatment and modified agent addition, prepare the characteristic carbon material to reduce the orientation and expansion rate of the material.
It significantly improves the cycle life and fast charge performance of the negative electrode materials, reduces the expansion rate, and maintains the rapid transmission of lithium ions, extending the long cycle life of the battery.
Smart Images

Figure CN119361668A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials for lithium-ion batteries, and more specifically, to a negative electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Graphite is the mainstream negative electrode material for lithium-ion batteries on the current market. According to different sources, graphite can be divided into artificial graphite and natural graphite. Among them, artificial graphite occupies most of the power battery market with its good cycle stability. The advantages of natural graphite are high capacity and low carbon emissions, but short cycle life. At present, natural graphite is usually modified by surface coating, coating a layer of amorphous carbon on its surface, and isolating the electrolyte and natural graphite in the battery to improve its performance. This method is simple to operate and low in cost, and is widely used in the modification of natural graphite negative electrode materials. However, since the coating agent cannot completely cover the outer surface of natural graphite (especially the surface of flake graphite inside spherical graphite), the electrolyte will gradually penetrate into these uncoated natural graphite surfaces during the cycle, continuously generate SEI (solid electrolyte interface) and the electrolyte is continuously embedded in the natural graphite layer structure, which will consume a large amount of active lithium, destroy the natural graphite structure, and cause continuous capacity decay. Therefore, it is necessary to develop a new method for modifying natural graphite. The natural graphite particles are densified or isotropically processed and the pore size is controlled to reduce the porosity of the natural spherical graphite particles and the orientation of the particles, thereby reducing the expansion rate of the material and improving the cyclic performance of the material.
[0003] Based on this, it is necessary to provide a negative electrode material and a preparation method thereof, so that the cycle life and fast charging performance of the battery prepared therefrom are improved, and the orientation and expansion rate are also improved. Summary of the invention
[0004] In order to at least solve one or more of the technical problems mentioned above, the present application proposes negative electrode materials, methods for preparing negative electrode materials, and solutions for lithium-ion batteries in multiple aspects.
[0005] According to one aspect of the present application, a negative electrode material is provided, which includes a carbon material; wherein the carbon material has pores therein, and the pores have the following characteristics: for pores with a pore diameter of greater than 3 nm and less than 1000 nm, a pore volume obtained by mercury porosimetry is V1, and V1<0.1 mL / g; for pores with a pore diameter of greater than 3 nm and less than 400 nm, a pore volume obtained by mercury porosimetry is V2, and a ratio range of V2 / V1 satisfies 40%~70%; for pores with a pore diameter of greater than 3 nm and less than 500 nm, a pore volume obtained by mercury porosimetry is V3, and a ratio range of V3 / V1 satisfies ≥60%.
[0006] According to one embodiment of the present application, in the XRD spectrum of the negative electrode material, there is a 004 peak between 2θ of 54°-55°, and the intensity of the 004 peak is I 004 ; There is a 110 peak between 77°-78° at 2θ, and the intensity of the 110 peak is I 110 ; The ratio of the two intensities I 004 / I 110 ≤3.0.
[0007] According to one embodiment of the present application, the negative electrode material includes at least one of the following features: a. BET specific surface area ≤ 3.0 m 2 / g; b. The volume median particle size Dv50 ranges from 5μm to 25μm; c. The compacted density ranges from 1.5-2.1 g / cc; d. The tap density ranges from 0.9-1.2 g / cc; e. The fixed carbon content range is ≥99.94%.
[0008] According to one embodiment of the present application, the carbon material includes natural graphite.
[0009] According to another aspect of the present application, a method for preparing a negative electrode material is provided, comprising: a first step of selecting a carbon material raw material, crushing and spheroidizing the carbon material raw material; a second step of performing pore control treatment on the carbon material obtained in the first step; and a third step of performing high-temperature heat treatment on the carbon material obtained in the second step. The pore control treatment includes any one or a combination of at least two of adding a modifier, fusion heating, reactor heating, rolling, cold isostatic pressing, hot isostatic pressing or molding.
[0010] According to one embodiment of the present application, the carbon material raw material is selected from one or more of natural spherical graphite, natural flake graphite or microcrystalline graphite.
[0011] According to one embodiment of the present application, in the first step, the spheroidization treatment further includes a purification treatment step.
[0012] According to one embodiment of the present application, in the second step, the pore regulation treatment includes adding a modifier, and the modifier is selected from any one of resin, coal tar, petroleum asphalt, mesophase asphalt, coal tar or heavy oil, glucose, sucrose, starch, polydopamine, polyvinyl alcohol, polypyrrole, polyethylene glycol, anthracene, aniline, citric acid, acetic acid, and tannic acid, or a combination of at least two thereof.
[0013] According to one embodiment of the present application, the third step includes at least one of the following features: a. The high temperature heat treatment is carried out at a temperature of 600 ℃ -3000 ℃; b. The high temperature heat treatment is carried out in an inert gas atmosphere, wherein the inert gas is any one of helium, neon, argon, nitrogen or krypton, or a combination of at least two of them.
[0014] According to another aspect of the present application, a lithium-ion battery is provided, comprising the negative electrode material of any of the aforementioned embodiments or the negative electrode material prepared according to the preparation method of any of the aforementioned embodiments.
[0015] The technical solution of the embodiment of the present application reduces the pore volume of the negative electrode material and adjusts the pore size distribution of the residual pores, which not only maintains the low pore volume of the negative electrode material, improves the cycle life of the negative electrode material and reduces the expansion rate, but also retains some mesopores to maintain the rapid transmission of lithium ions in the material. By regulating the pore volume and pore volume distribution of the negative electrode material, the technical solution of the embodiment of the present application reduces the orientation of the negative electrode material, effectively reduces the expansion of the negative electrode material during the cycle and improves the long cycle life of the battery, while keeping the negative electrode material at a low impedance, effectively improving the fast charging performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present application will become easy to understand. In the accompanying drawings, several embodiments of the present application are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein: Figure 1 shows a schematic diagram of a battery in a discharged state; Figure 2 The pore volume distribution diagrams of the carbon materials of Example 1 and Comparative Example 1 of the present application are shown. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0018] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0019] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.
[0020] As used in this specification and claims, the term "if" can be interpreted as "when" or "upon" or "in response to determining" or "in response to detecting," depending on the context. Similarly, the phrases "if it is determined" or "if [described condition or event] is detected" can be interpreted as meaning "upon determination" or "in response to determining" or "upon detection of [described condition or event]" or "in response to detecting [described condition or event]," depending on the context.
[0021] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.
[0022] An embodiment of the present application provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), comprising a housing, an electrode assembly, and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing.
[0023] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0024] Figure 1 A schematic diagram of a battery in a discharge state, i.e., during operation, is shown. As shown in the figure, the electrode assembly includes a positive electrode sheet 110, a negative electrode sheet 120, and a separator 130, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence and then winding them.
[0025] Positive electrode The positive electrode sheet 110 includes a positive electrode current collector 111 and a positive electrode active layer 112 disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active layer contains a positive electrode active material, and the positive electrode active material includes a compound that reversibly embeds and deintercalates metal ions. In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, and the like. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0026] Negative plate The negative electrode sheet 120 includes a negative electrode current collector 121 and a negative electrode active material layer 122 disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode material.
[0027] During battery operation, that is, when the battery is in a discharge state, metal ions 140 (eg, lithium ions) in the negative electrode are released from the lattice of the negative electrode material, pass through the separator 130 through the electrolyte / electrolyte, and are embedded in the lattice of the positive electrode material.
[0028] Conversely, when the battery is charged by applying an external circuit, the oxidation of the positive electrode material causes the metal ions (such as lithium ions) in the positive electrode to escape from the lattice of the positive electrode material, pass through the isolation membrane through the electrolyte / electrolyte, and move to the negative electrode; at the same time, the negative electrode material undergoes a reduction reaction, causing the metal ions to be embedded in the lattice of the negative electrode material.
[0029] As metal ions move back and forth between the positive and negative electrodes, the battery can be discharged and charged thousands of times.
[0030] The present application provides a negative electrode material, which includes a carbon material; wherein the carbon material has pores, and the pores have the following characteristics: for pores with a pore diameter of greater than 3 nm and less than 1000 nm, a pore volume obtained by mercury porosimetry is V1, and V1<0.1 mL / g; for pores with a pore diameter of greater than 3 nm and less than 400 nm, a pore volume obtained by mercury porosimetry is V2, and a ratio range of V2 / V1 satisfies 40%~70%; for pores with a pore diameter of greater than 3 nm and less than 500 nm, a pore volume obtained by mercury porosimetry is V3, and a ratio range of V3 / V1 satisfies ≥60%.
[0031] In the process of spheroidization of existing natural graphite negative electrode materials, many pores are formed inside the particles of spherical graphite due to the curling and stacking of scales. The pore volume and specific surface area of the material are relatively high, and there are many surface defects. The technical solution of the present application reduces the pore volume of the material, and at the same time controls the pore size distribution of the residual pores, which not only maintains the low pore volume of the material, improves the cycle life of the material and reduces the cycle expansion, but also retains some mesopores and maintains the rapid transmission of lithium ions in the material. The technical solution of the present application reduces the orientation of the material by regulating the pore volume and pore volume distribution of the material; the lower pore volume and specific pore volume distribution can effectively reduce the expansion of the negative electrode material during the cycle and improve the long cycle life of the battery, while keeping the material at a lower impedance and effectively improving the fast charging performance of the material. When the pore volume and pore volume distribution do not meet the target range, the contact and consumption of the material with the electrolyte will increase, the SEI film formed will be thicker, the amount of electrolyte will be reduced, resulting in a significant decrease in the cycle life of the material, an increase in the expansion rate of the pole piece, and a larger pore size may cause the mechanical stability of the electrode material to decrease, thereby affecting the cycle life and safety of the battery.
[0032] Specifically, when V1≥0.1 mL / g, the carbon material will have more contact with the electrolyte, which will consume more electrolyte, resulting in less electrolyte and thicker SEI film, which will significantly reduce the cycle life of the material and increase the expansion rate of the pole piece. When V2 / V1<40% or V3 / V1<60%, the pores inside the material are too concentrated in the range of pore diameter 500nm~1000nm. Excessive pore diameter may reduce the mechanical stability of the electrode material and increase the contact and consumption of the electrolyte, thereby affecting the cycle life and safety of the battery. When V2 / V1>70%, the pores inside the material are too concentrated in the range of pore diameter 3nm~400nm. Excessively small pore diameter is not conducive to the rapid transmission of lithium ions, making the material impedance larger, accelerating the temperature rise of the battery, accelerating the decomposition and consumption of the electrolyte, resulting in a larger expansion rate of the pole piece of the material and a lower cycle retention rate of the battery.
[0033] In some embodiments, in the XRD spectrum of the negative electrode material (XRD is the abbreviation of "X-ray diffraction": X-ray diffraction is an optical analysis method detected by an instrument, where monochromatic X-rays are irradiated onto a powder crystal sample, and if a set of face-net orientations of one of the crystal grains is at an angle θ with the incident X-rays, diffraction is generated at a diffraction angle of 2θ, and the diffraction condition is satisfied), there is a 004 peak between 2θ of 54° and 55°, and the intensity of the 004 peak is I 004 ; There is a 110 peak between 77°-78° at 2θ, and the intensity of the 110 peak is I 110 ; The ratio of the two intensities I 004 / I 110 ≤3.0. For example, I 004 / I 110 It can be 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.8, 1.6, 1.4, 1.2 or any value within the range of any of the above values. The technical solution of the present application reduces the orientation of the material by regulating the pore size distribution, which is beneficial to the rapid transmission of lithium ions and can effectively improve the fast charging performance of the material. When the ratio I 004 / I 110 >3. The orientation of the material is enhanced, which is not conducive to the rapid transmission of lithium ions. The material impedance is large, which accelerates the temperature rise of the battery, the decomposition and consumption of the electrolyte, and causes the expansion rate of the material to increase, thus affecting the cycle life of the battery.
[0034] In some embodiments, the BET specific surface area of the negative electrode material is ≤3.0 m 2 / g, which can be 3.0 m 2 / g, 2.9m 2 / g, 2.8m 2 / g, 2.7m 2 / g, 2.6m 2 / g, 2.5m 2 / g, 2.4m 2 / g, 2.3m 2 / g, 2.0m 2 / g, 1.5m 2 / g, 1.0 m 2 / g, 0.5 m 2 / g or any value within the range formed by any of the above values. When the BET specific surface area falls within the above range, the lower specific surface area is conducive to the material to achieve a higher first coulombic efficiency, so that the battery cycle life prepared by the negative electrode material is improved and has better high temperature storage performance.
[0035] In some embodiments, the volume median particle size Dv50 of the negative electrode material ranges from 5 μm to 25 μm, and can be 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, or any value within the range composed of any of the above values. If the average particle size of the negative electrode material is less than 5 μm, it is not conducive to the rapid transmission of lithium ions in the negative electrode material, so that the material impedance becomes larger and the cycle retention rate of the battery is reduced. If the average particle size of the negative electrode material is greater than 25 μm, the particle size of the negative electrode material is too large, so that the space between the particles of the negative electrode material is larger, which may affect the mechanical properties of the material, thereby affecting the cycle life of the battery. When Dv50 falls within the above range, it is beneficial for the material to exert a higher first coulomb efficiency, so that the cycle life of the battery prepared by the negative electrode material is improved and has better high temperature storage performance.
[0036] In some embodiments, the compaction density of the negative electrode material is in the range of 1.5-2.1 g / cc, and the compaction density of the negative electrode material can be 1.50 g / cc, 1.55 g / cc, 1.60 g / cc, 1.65 g / cc, 1.70 g / cc, 1.75 g / cc, 1.80 g / cc, 1.85 g / cc, 1.90 g / cc, 1.95 g / cc, 2.0 g / cc, 2.05 g / cc, 2.10 g / cc or any value within the range of any of the above values. When the compaction density falls within the above range, the material has a higher compaction density, so that the energy density of the battery prepared by the negative electrode material is improved.
[0037] In some embodiments, the tap density of the negative electrode material is in the range of 0.9-1.2 g / cc, and the compacted density of the negative electrode material can be 0.90 g / cc, 0.92 g / cc, 0.95 g / cc, 0.98 g / cc, 1.0 g / cc, 1.02 g / cc, 1.05 g / cc, 1.08 g / cc, 1.10 g / cc, 1.12 g / cc, 1.15 g / cc, 1.18 g / cc, 1.20 g / cc or any value within the range of any of the above values. When the tap density falls within the above range, the material has a higher tap density, so that the slurry prepared by the negative electrode material in the process of preparing the negative electrode slurry has better stability and consistency.
[0038] In some embodiments, the fixed carbon content of the negative electrode material is in the range of ≥99.94%, and the fixed carbon content of the negative electrode material can be 99.94%, 99.95%, 99.96%, 99.97%, 99.98%, 99.99% or any value in the range formed by any of the above values. When the fixed carbon content falls within the above range, the higher fixed carbon content enables the negative electrode material to have a higher capacity, and the battery prepared therefrom has better high temperature storage performance.
[0039] In some embodiments, the expansion rate of the negative electrode sheet made of the negative electrode material after 20 cycles is less than 27%, and can be 26.5%, 26%, 25.5%, 25%, 24.5%, 24%, 23.5%, 23%, 22.5%, 22%, 21%, 20% or any value within the range formed by any of the above values. The expansion rate of the electrode sheet after 20 cycles reflects the expansibility of the material during use. By regulating the pore volume and pore distribution, the negative electrode sheet made of the negative electrode material of the present application has significantly reduced expansibility.
[0040] In some embodiments, the 1C / 1C cycle 300-week capacity retention rate of the soft-pack battery made of the negative electrode material is greater than 85%, and can be 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93% or any value within the range formed by any of the above values. The 1C / 1C cycle 300-week capacity retention rate reflects the cyclic performance of the material in use. The present application significantly improves the capacity retention rate of the battery made of the material by regulating the pore volume and pore distribution.
[0041] In some embodiments, the carbon material includes natural graphite. The present application reduces the porosity of natural graphite, densifies or isotropically modulates the pore volume and pore distribution, while maintaining a certain amount of mesopores, thereby reducing the expansion rate of the material and improving the cyclic performance of the material.
[0042] Figure 2 The pore volume distribution diagrams of the carbon materials of Example 1 and Comparative Example 1 of the present application are shown.
[0043] The present application also provides a method for preparing a negative electrode material, comprising: a first step S1, selecting a carbon material raw material, and crushing and spheroidizing the carbon material raw material; a second step S2, performing pore control treatment on the carbon material obtained in the first step; a third step S3, performing high-temperature heat treatment on the carbon material obtained in the second step; the pore control treatment comprises adding a modifier, fusion heating, reactor heating, rolling, cold isostatic pressing, hot isostatic pressing or molding treatment, or a combination of at least two of them.
[0044] The technical solution of the present application accurately controls the pore volume and pore size distribution of the material through steps such as pore control treatment. On the one hand, it maintains a low pore volume of the material, improves the cycle life of the material and reduces the expansion rate of the material. On the other hand, it retains some mesopores to ensure the rapid transmission of lithium ions in the material, thereby making the material have a lower impedance and effectively improving the fast charging performance of the material.
[0045] In some embodiments, in the first step, the selected carbon material raw material may be highly crystalline graphite; the carbon material raw material is selected from one or more of natural spherical graphite, natural flake graphite or microcrystalline graphite.
[0046] In some embodiments, in the first step, the pulverization is carried out by mechanical pulverization.
[0047] In some embodiments, in the first step, the spheroidization treatment is followed by a purification step. Preferably, the purification treatment is carried out by acid purification.
[0048] In some embodiments, the carbon material obtained in the first step is spherical natural graphite with a Dv50 of 5 μm-25 μm; preferably, the carbon material obtained in the first step is spherical natural graphite with a Dv50 of 9 μm-18 μm.
[0049] In some embodiments, in the second step, preferably, the pore regulation treatment includes any one of adding a modifier, fusion heating, cold isostatic pressing or molding treatment, or a combination of at least two. For example, the pore regulation treatment is a combination of cold isostatic pressing treatment followed by adding a modifier. Cold isostatic pressing treatment can reduce the total pore volume and densify the material. Heat treatment followed by adding a modifier can maintain a certain number of mesopores in the material, which is beneficial to the transmission of lithium ions and improves the fast charging performance of the material. The method of molding treatment first and then adding a modifier can also achieve the technical effect described above.
[0050] In some embodiments, in the second step, the pore control treatment is a combination of cold isostatic pressing treatment and then adding a modifier. Specifically, the carbon material obtained in the first step is placed in a cold isostatic press for treatment, and the working pressure of the cold isostatic press is 60MPa-70MPa; the specific setting of the pressure curve is: the pressure rises from 0MPa to 20MPa-30MPa in 8min-12min, the holding time is 5min-10min, and the pressure rises to 60MPa-70MPa in 25-45min, and the holding time is 5min-8min, to obtain block graphite; the block graphite is crushed to obtain graphite with a Dv50 of 9μm-16μm, and it is mixed with the modifier at a mass ratio of 100:5-20.
[0051] In some embodiments, in the second step, the pore control treatment is a combination of first molding treatment and then adding a modifier. Specifically, the carbon material obtained in the first step is placed in a molding machine for processing, and the working pressure of the molding machine is 20 MPa-25MPa; the specific setting of the pressure curve is: 8min-12min pressure rises from 0MPa to 10MPa-15MPa, the holding time is 4min-5min, 15min-20min rises to 20MPa-25MPa, the holding time is 10min-15min, and block graphite is obtained; the block graphite is crushed to obtain graphite with a Dv50 of 5μm-20μm, and it is mixed with the modifier at a mass ratio of 100:5-20.
[0052] In some embodiments, in the second step, the pore control treatment is a combination of adding a modifier first and then fusion heating. Specifically, the carbon material obtained in the first step is mixed with the modifier in a mass ratio of 100:5-20, put into a fusion machine, heated to 180°C-220°C at a heating rate of 3°C / min-7°C / min, a rotation speed of 1800r / min-2200r / min, maintained for 1.5 hours-2.5 hours, and cooled to room temperature.
[0053] In some embodiments, in the second step, the pore control treatment includes adding a modifier. The modifier is selected from any one or a combination of at least two of resin, coal tar, petroleum asphalt, mesophase asphalt, coal tar or heavy oil, glucose, sucrose, starch, polydopamine, polyvinyl alcohol, polypyrrole, polyethylene glycol, anthracene, aniline, citric acid, acetic acid, and tannic acid. Preferably, the modifier is selected from any one or a combination of at least two of resin, coal tar, petroleum asphalt, and mesophase asphalt. Preferably, the amount of the modifier added is 5wt%-20wt% based on the weight of the carbon material.
[0054] In some embodiments, in the third step, the high temperature heat treatment is carried out at a temperature of 600°C-3000°C; illustratively, the temperature of the high temperature heat treatment can be 800°C, 1000°C, 1200°C, 1500°C, 1800°C, 2100°C, 2300°C, 2500°C, 2800°C or any value within the range formed by any two of the above values.
[0055] In some embodiments, specifically, in the third step, the temperature curve of the high temperature heat treatment can be: heating to 200°C at a heating rate of 3°C / min-7°C / min, and keeping constant at 200°C for 25min-35min, heating to 600°C at a heating rate of 1.5°C / min-2.5°C / min, and keeping constant at 600°C for 25min-35min, heating to 1000°C-1200°C at a heating rate of 8°C / min-12°C / min, and keeping constant at 1000°C-1200°C for 180min-220min.
[0056] In some embodiments, specifically, in the third step, the temperature curve of the high temperature heat treatment can be: heating to 1200°C at a heating rate of 8°C / min-12°C / min, and keeping constant at 1200°C for 25min-35min, heating to 1800°C at a heating rate of 8°C / min-12°C / min, heating to 2300°C-2800°C at a heating rate of 15°C / min-25°C / min, and keeping constant at 2300°C-2800°C for 50min-70min.
[0057] In some embodiments, in the third step, the high temperature heat treatment is performed in an atmosphere of an inert gas. Preferably, the inert gas is any one of helium, neon, argon, nitrogen or krypton, or a combination of at least two of them. The inert gas atmosphere protection is beneficial to the material preparation process.
[0058] According to another aspect of the present application, a lithium ion battery is provided, comprising the aforementioned negative electrode material or the negative electrode material prepared according to the aforementioned preparation method. The aforementioned lithium ion battery has reduced expansion, and at the same time has good cycle life and fast charging performance.
[0059] Specific Examples and Comparative Examples Example 1 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 9 μm.
[0060] The second step S2: the high-purity spherical natural graphite is placed in a cold isostatic press for processing, and the working pressure of the isostatic press is set as follows: the pressure rises from 0 MPa to 30 MPa in 10 minutes, the holding time at 30 MPa is 5 minutes, and the pressure rises to 60 MPa in 25 minutes, and the holding time is 8 minutes, to obtain block graphite. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 9 μm. The obtained graphite is mixed with asphalt at a mass ratio of 100:10.
[0061] The third step S3: the mixed material is then subjected to a high-temperature treatment at 1200°C in a nitrogen atmosphere to obtain a carbon material. The specific temperature curve of the high-temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and maintaining a constant temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and maintaining a constant temperature at 600°C for 30 minutes, heating to 1200°C at a heating rate of 10°C / min, and maintaining a constant temperature at 1200°C for 200 minutes.
[0062] Example 2 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 18 μm.
[0063] Step 2 S2: The high-purity spherical natural graphite is placed in a molding machine for processing, and the working pressure is set as follows: the pressure rises from 0 MPa to 10 MPa in 10 minutes, the 10 MPa is maintained for 5 minutes, and the pressure rises to 20 MPa in 15 minutes, and the maintenance time is 10 minutes, to obtain block graphite. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 18 μm. The obtained graphite is mixed with asphalt at a mass ratio of 100:5.
[0064] The third step S3: The mixed material is then subjected to a high-temperature treatment at 1000°C in a nitrogen atmosphere to obtain a carbon material. The specific temperature curve of the high-temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and maintaining a constant temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and maintaining a constant temperature at 600°C for 30 minutes, heating to 1000°C at a heating rate of 10°C / min, and maintaining a constant temperature at 1000°C for 200 minutes.
[0065] Example 3 The first step S1: natural flake graphite is selected and mechanically crushed and spheroidized to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 17 μm.
[0066] Second step S2: Mix the obtained graphite and asphalt in a mass ratio of 100:6 and put them into a fusion machine, heat to 200° C. at 5° C. / min, rotate at 2000 r / min, keep for 2 hours, and cool to room temperature.
[0067] The third step S3: The mixed material is then treated at a high temperature of 1200°C to obtain a carbon material. The specific temperature curve of the high temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and keeping the temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and keeping the temperature at 600°C for 30 minutes, heating to 1200°C at a heating rate of 10°C / min, and keeping the temperature at 1200°C for 200 minutes.
[0068] Example 4 The first step S1: microcrystalline graphite is selected and mechanically crushed and spheroidized to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 10 μm.
[0069] The second step S2: the high-purity spherical natural graphite is placed in a cold isostatic press for processing, and the working pressure of the isostatic press is set to: the pressure rises from 0 MPa to 20 MPa in 10 minutes, the holding time of 20 MPa is 5 minutes, the pressure rises to 50 MPa in 20 minutes, the holding time is 10 minutes, the pressure rises to 80 MPa in 10 minutes, the holding time is 5 minutes, the pressure rises to 120 MPa in 15 minutes, the holding time is 5 minutes, the pressure rises to 150 MPa in 10 minutes, the holding time is 1 minute, and block graphite is obtained. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 10 μm. The obtained graphite is mixed with asphalt in a mass ratio of 100:20.
[0070] The third step S3: The mixed material is then treated at a high temperature of 2800°C to obtain a carbon material. The specific temperature curve of the high temperature treatment is: heating to 1200°C at a heating rate of 10°C / min, and keeping the temperature at 1200°C for 30 minutes, heating to 1800°C at a heating rate of 10°C / min, heating to 2800°C at a heating rate of 20°C / min, and keeping the temperature at 1200°C for 60 minutes.
[0071] Example 5 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 16 μm.
[0072] Step 2 S2: The high-purity spherical natural graphite is placed in a cold isostatic press for processing. The working pressure of the isostatic press is set to: the pressure rises from 0 MPa to 30 MPa in 10 minutes, the pressure is maintained at 30 MPa for 5 minutes, and the pressure rises to 70 MPa in 45 minutes, and the pressure is maintained for 5 minutes to obtain block graphite. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 16 μm. The obtained graphite is mixed with phenolic resin at a mass ratio of 100:8.
[0073] The third step S3: The mixed material is then treated at a high temperature of 2300°C to obtain a carbon material. The specific temperature curve of the high temperature treatment is: heating to 1200°C at a heating rate of 10°C / min, and keeping the temperature at 1200°C for 30 minutes, heating to 1800°C at a heating rate of 10°C / min, heating to 2300°C at a heating rate of 20°C / min, and keeping the temperature at 1200°C for 60 minutes.
[0074] Example 6 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 10 μm and Dv90 / Dv10=2.0.
[0075] The second step S2: the high-purity spherical natural graphite is placed in a cold isostatic press for processing, and the working pressure of the isostatic press is set as follows: the pressure rises from 0 MPa to 50 MPa in 30 minutes, and the holding time is 10 minutes, and the pressure rises to 150 MPa in 30 minutes, and the holding time is 5 minutes, and the pressure rises to 200 MPa in 25 minutes, and the holding time is 1 minute, to obtain block graphite. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 10 μm and Dv90 / Dv10=2.0. The obtained graphite is mixed with asphalt in a mass ratio of 100:15.
[0076] The third step S3: The mixed material is then treated at a high temperature of 1200°C to obtain a carbon material. The specific temperature curve of the high temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and keeping the temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and keeping the temperature at 600°C for 30 minutes, heating to 1200°C at a heating rate of 10°C / min, and keeping the temperature at 1200°C for 200 minutes.
[0077] Comparative Example 1 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 9 μm.
[0078] Compared with the embodiment, a simplified second step S2 is performed: the high-purity spherical natural graphite is mixed with asphalt in a mass ratio of 100:10.
[0079] The third step S3: the mixed material is then subjected to a high-temperature treatment at 1200°C in a nitrogen atmosphere to obtain a carbon material. The specific temperature curve of the high-temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and maintaining a constant temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and maintaining a constant temperature at 600°C for 30 minutes, heating to 1200°C at a heating rate of 10°C / min, and maintaining a constant temperature at 1200°C for 200 minutes.
[0080] Comparative Example 2 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 18 μm.
[0081] Without performing the second step S2, the third step S3 is performed directly: the high-purity spherical natural graphite is subjected to high-temperature treatment at 1000°C in a nitrogen atmosphere to obtain a carbon material, and the specific temperature curve of the high-temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and maintaining the temperature at 200°C for 30 min, heating to 600°C at a heating rate of 2°C / min, and maintaining the temperature at 600°C for 30 min, heating to 1000°C at a heating rate of 10°C / min, and maintaining the temperature at 1000°C for 200 min.
[0082] Comparative Example 3 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 18 μm.
[0083] Compared with the embodiment, a simplified second step S2 is performed: the high-purity spherical natural graphite is mixed with asphalt in a mass ratio of 100:15.
[0084] The third step S3: the mixed material is then treated at a high temperature of 1200°C under a nitrogen atmosphere to obtain a carbon material after depolymerization (the "depolymerization" in the above text refers to the fact that after the natural graphite and asphalt are mixed and carbonized, some graphite particles will be bonded together due to the adhesiveness of the asphalt, and the particles that are bonded together need to be separated by mechanical equipment). The specific temperature curve of the high-temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and keeping the temperature at 200°C for 30 minutes, heating to 600°C at a heating rate of 2°C / min, and keeping the temperature at 600°C for 30 minutes, heating to 1200°C at a heating rate of 10°C / min, and keeping the temperature at 1200°C for 200 minutes.
[0085] Comparative Example 4 The first step S1: natural flake graphite is selected and subjected to mechanical crushing, spheroidization, and acid purification to obtain high-purity spherical natural graphite with a volume median particle size Dv50 of 18 μm.
[0086] The second step S2: the high-purity spherical natural graphite is mixed with asphalt in a mass ratio of 100:6, and then the mixture is placed in a cold isostatic press for processing. The working pressure of the isostatic press is set to: the pressure rises from 0 MPa to 30 MPa in 10 minutes, the 30 MPa is maintained for 5 minutes, and the pressure rises to 60 MPa in 25 minutes, and the maintenance time is 8 minutes, to obtain block graphite.
[0087] The third step S3: a high temperature treatment of 1200°C is performed under a nitrogen atmosphere to obtain a carbon material, and the specific temperature curve of the high temperature treatment is: heating to 200°C at a heating rate of 5°C / min, and maintaining the temperature at 200°C for 30min, heating to 600°C at a heating rate of 2°C / min, and maintaining the temperature at 600°C for 30min, heating to 1200°C at a heating rate of 10°C / min, and maintaining the temperature at 1200°C for 200min. The block graphite is crushed and pulverized to obtain graphite with a particle volume median particle size Dv50 of 18μm.
[0088] The test methods used in this application are as follows: The volume median particle size Dv50 of the material was tested using Malvern laser particle size tester MS 3000; The specific surface area test was carried out using the Tristar equipment from Micromeritics.
[0089] The pore volume is tested using a mercury porosimeter Micromeritics AutoPore IV 9500 to measure the pore volume within the pore diameter range of 3-1000 nm, the pore volume within the pore diameter range of 3-400 nm, the pore volume within the pore diameter range of 3-500 nm, and the like.
[0090] X-ray diffractometer was used for XRD test, and the intensity of 004 peak (2θ=54.6°) and 110 peak (2θ=77.4°) was selected for ratio to obtain the powder orientation (I 004 / I 110 ) is the value of .
[0091] The pole piece expansion rate test uses the test device and system disclosed in patent application CN201920973729.5 to test the pole piece expansion rate for 20 cycles.
[0092] The compaction density of the material under 1.0T pressure was tested using an automatic compaction density meter.
[0093] The tap density of the material was tested using the American Quantachrome Auto Tap instrument, with a sample volume of 100 mL, 1000 vibrations, and a vibration frequency of 260 times / min.
[0094] The fixed carbon content is tested according to GB / T 3521-2008 “Chemical Analysis Methods for Graphite”.
[0095] Battery test: The provided carbon material, conductive agent SP, CMC and SBR are mixed in a mass ratio of 95.9:1.0:1.3:1.8 and coated on copper foil to obtain a negative electrode; the positive electrode active material NCM523, conductive agent SP, conductive agent CNTs, PVDF are mixed in a mass ratio of 97.0:1.0:0.5:1.5 and coated on aluminum foil to obtain a positive electrode; the electrolyte is 1 mol / LLiPF6+EC+EMC, and the diaphragm is a PP / PE / PP three-layer diaphragm. A soft-pack battery of about 38mAh is made to test the full battery performance of the material. The 1C / 1C capacity retention rate test method is: 1C charging and 1C discharging are continuously charged and discharged for 300 weeks.
[0096] Table 1 shows the test results of various embodiments and comparative examples.
[0097] Table 1
[0098] It can be seen from the results in the above table that the carbon material prepared by this scheme satisfies V1 reduced to <0.1mL / g, the V2 / V1 ratio range satisfies 40%~70%, and the V3 / V1 ratio range satisfies ≥60%; the carbon material formed in this way has an overall lower pore volume, wherein the pore diameter is mostly concentrated in the range of 3nm~500nm, and there are a moderate amount of pores with a moderate pore diameter of 400~500nm, and there are also a moderate amount of pores with a larger pore diameter of 500nm~1000nm, which not only ensures the rapid transmission of lithium ions, but also ensures a more stable structure of the material; the expansion of the electrode sheet of the material in the battery for 20 weeks has significantly decreased, reduced to less than 27%, and the lowest can reach 23.8%; the capacity retention rate of 300 cycles has increased by more than 5%, which effectively reduces the expansion of the negative electrode material during the cycle and improves the long cycle life of the battery, while keeping the material at a low impedance, effectively improving the fast charging performance of the material.
[0099] It can be seen from the results of Comparative Examples 1 and 2 and Examples 1 and 2 that since V1>0.1 mL / g in Comparative Examples 1 and 2, the material is in greater contact with the electrolyte and consumes more electrolyte, resulting in less electrolyte and a thicker SEI film. Even if V2 / V1 satisfies 40%~70% and V3 / V1 satisfies>60%, the cycle life of the material will be significantly reduced and the pole piece expansion rate will increase.
[0100] From the results of Comparative Example 3 (V2 / V1<40%, V3 / V1<60%), it is found that when only V1<0.1mL / g is satisfied but V2 / V1 is in the range of 40%~70% and V3 / V1≥60% cannot be satisfied at the same time, although the carbon material has an overall lower pore volume, the pores inside the material are too concentrated in the range of 500nm~1000nm. Excessive pore size may lead to reduced mechanical stability of the electrode material, increase the contact and consumption of the electrolyte, and also cause a significant decrease in the cycle life of the material and an increase in the expansion rate of the pole piece, thereby affecting the cycle life and safety of the battery.
[0101] From the results of Comparative Example 4 (V2 / V1>70%), it is found that when only V1<0.1mL / g and V3 / V1≥60% are satisfied, but V2 / V1 cannot be in the range of 40%~70% at the same time, there will be too few pores with a pore size of 500nm~1000nm inside the material, and too many pores will be concentrated in the range of 3nm~400nm. Too small pore size is not conducive to the rapid transmission of lithium ions, making the material impedance larger, accelerating the battery temperature rise, and accelerating the decomposition and consumption of the electrolyte, resulting in the material's electrode expansion rate still being large and the 300-week cycle retention rate being low.
[0102] The above experimental data show that the carbon material that meets the characteristics of the present application can effectively reduce the expansion of the electrode sheet and improve the cycle life of the battery when used as the negative electrode of the lithium-ion battery.
[0103] Although multiple embodiments of the present application have been shown and described herein, it is obvious to those skilled in the art that such embodiments are provided only by way of example. Those skilled in the art can think of many changes, modifications and alternatives without departing from the thought and spirit of the present application. It should be understood that in the process of practicing the present application, various alternatives to the embodiments of the present application described herein can be adopted. The attached claims are intended to limit the scope of protection of the present application, and therefore cover equivalents or alternatives within the scope of these claims.
Claims
1. A negative electrode material, comprising a carbon material, characterized in that: The carbon material has pores, and the pores have the following characteristics: for pores with a pore diameter of greater than 3 nm and less than 1000 nm, the pore volume obtained by mercury porosimetry is V1, and V1<0.1 mL / g; for pores with a pore diameter of greater than 3 nm and less than 400 nm, the pore volume obtained by mercury porosimetry is V2, and the ratio range of V2 / V1 satisfies 40%~70%; for pores with a pore diameter of greater than 3 nm and less than 500 nm, the pore volume obtained by mercury porosimetry is V3, and the ratio range of V3 / V1 satisfies ≥60%.
2. The negative electrode material according to claim 1, characterized in that In the XRD spectrum of the negative electrode material, there is a 004 peak between the diffraction peak angle 2θ of 54°-55°, and the intensity of the 004 peak is There is a 110 peak between the diffraction peak angle 2θ of 77°-78°, and the intensity of the 110 peak is The ratio of the two intensities .
3. The negative electrode material according to claim 1 or 2, characterized in that: The negative electrode material includes at least one of the following features: a.BET specific surface area ≤3.0 ; b. The volume median particle size Dv50 ranges from 5μm to 25μm; c. The compacted density ranges from 1.5-2.1 g / cc; d. The tap density ranges from 0.9-1.2 g / cc; e. The fixed carbon content range is ≥99.94%.
4. The negative electrode material according to claim 1 or 2, characterized in that: The carbon material includes natural graphite.
5. A method for preparing a negative electrode material, characterized in that: include: The first step is to select a carbon material raw material, and to crush and spheroidize the carbon material raw material; The second step is to perform pore control treatment on the carbon material obtained in the first step; The third step is to perform high temperature heat treatment on the carbon material obtained in the second step; The pore control treatment includes any one or a combination of at least two of adding a modifier, fusion heating, reactor heating, roller pressing, cold isostatic pressing, hot isostatic pressing or molding treatment.
6. The preparation method according to claim 5, characterized in that: In the first step, the carbon material raw material is selected from one or more of natural spherical graphite, natural flake graphite or microcrystalline graphite.
7. The preparation method according to claim 5 or 6, characterized in that: In the first step, the step of purification is further included after the spheroidization treatment.
8. The preparation method according to claim 5 or 6, characterized in that: In the second step, the pore regulation treatment includes adding a modifier, and the modifier is selected from any one of resin, coal tar, petroleum asphalt, mesophase asphalt, coal tar or heavy oil, glucose, sucrose, starch, polydopamine, polyvinyl alcohol, polypyrrole, polyethylene glycol, anthracene, aniline, citric acid, acetic acid, and tannic acid, or a combination of at least two thereof.
9. The preparation method according to claim 5 or 6, characterized in that: The third step includes at least one of the following features: a. The high temperature heat treatment is carried out at a temperature of 600°C-3000°C; b. The high temperature heat treatment is carried out in an inert gas atmosphere, wherein the inert gas is any one of helium, neon, argon, nitrogen or krypton, or a combination of at least two of them.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Battery pole piece thickness change measuring device and system
CN209991940U
Natural graphite-based modified composite material and preparation method thereof, and lithium ion battery comprising modified composite material
CN108063229A
High-capacity fast-charging type microcrystal graphite negative electrode material and preparation method thereof
CN110416497A
Negative pole piece and lithium ion battery comprising same
CN115663116A
Negative electrode material and battery
CN117558917A
Cited By
Negative electrode material and lithium-ion battery
WO2026130094A1